Typographic design form and communication - Carter, Rob; Maxa, Sandra; Sanders, Mark; Meggs, Philip B.; Day, Ben (Wiley, 2018)
"This book is the definitive reference for graphic designers, providing a comprehensive introduction to the visual word. Done well, type can communicate so much more than the words themselves; in fact, the written words and the "real" message can be at odds. Typography design determines how you feel about a message, the associations you make, and ultimately, the overall success of the piece. Typography design extends from the page to the screen, and is a critical element of almost any graphic design project. This book provides essential guidance on everything related to type: from letterforms and negative space, to messaging, processes, and history, aspiring designers will find great utility in mastering these critical concepts"-- Provided by publisher.